(untitled) (Journal of actual problems of jurisprudence, 2016)
The paper deals with allocation and the delimitation of powers of natural resource management in post-conflict societies. Clear distinction in the management of natural resources is an important source of stability. The article analyzes the constitutional norms of different countries, delineates the powers over natural resources. Moreover paper also considers the constitutional legal agreement between the conflicting parties as a source which deals with questions of nature use. From this perspective, it is important that a clear definition of right of governance is one of the most important aspects of public consent.